Warisan Khunśa dan Relevansi Pandangan Ulama Syafi’iyah di Masa Kini - Lia Dahliani (TAHKIM, 2017)
This study confirmed that in relation to inheritance, khunsa (hermaphrodites) got the part and the different divisions and they tend to get a smaller share of the inheritance. This paper discussed the legacy of khunsa in the discourse of Shafi’ites and its relevance in solving the inheritance issues in the contemporary era. The main sources of this paper are Shafi’ite’s books such as Al-Hawi al-Kabir written by Abu Hasan al-Mawardi Al-Basri, Mughni al-Muhtaj written al-Syarbaini, Majmu’ Syarh al-Muhaźźab by Imam an-Nawawi and so on. This is a library research. It used a philosophical approach. Descriptive and explanatory were used as analysis method. According to Syafi’iyahs, if gender status of khunsa remains intractable (musykil), then his or her inheritance is suspended until there is mutual agreement between the heirs. Keyword: inheritance, khunsa, Shafi’ites, contemporary era